2015
DOI: 10.1108/amhid-06-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Clinician experiences of administering the Essen Climate Evaluation Schema (EssenCES) in a forensic intellectual disability service

Abstract: Purpose -Social climate (ward atmosphere) affects numerous treatment outcomes. The most commonly used measure is the Essen Climate Evaluation Schema (EssenCES) (Schalast et al., 2008). Though studies have investigated the psychometric properties of EssenCES in intellectual disability populations, few have focused on the clinical utility, or accessibility of the measure. The purpose of this paper is to examine clinician's experiences of using this measure with this population. Design/methodology/approach -Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The suitability of the EssenCES for IDD populations has been questioned in a recent study which investigated clinician experiences of using the EssenCES in forensic IDD settings (Chester et al, 2015). Participants were seven clinicians currently working, or who had previously worked, within the Psychology discipline in one UK forensic IDD service.…”
Section: Measurement Of the Social Climate In Id Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The suitability of the EssenCES for IDD populations has been questioned in a recent study which investigated clinician experiences of using the EssenCES in forensic IDD settings (Chester et al, 2015). Participants were seven clinicians currently working, or who had previously worked, within the Psychology discipline in one UK forensic IDD service.…”
Section: Measurement Of the Social Climate In Id Settingsmentioning
confidence: 99%
“…Secondly, the resulting reduction in anonymity of responses can increase the likelihood of nay-saying or socially desirable responding when individuals are asked questions regarding prohibited behaviour or the quality of their care (Finlay & Lyons, 2001). Lastly, it has been suggested that oral presentation of questionnaire measures can lead to administrating staff providing further explanation of the questions, resulting in concerns surrounding staff projecting their own interpretation of a question on to individuals (Chester et al, 2015).…”
Section: Response Biases Response Format Difficulties and Questionnamentioning
confidence: 99%
See 1 more Smart Citation
“…This would involve adapting the measure to improve its appropriateness for an intellectual disability population. This has previously been proposed by Chester et al (2015), who posited that the EssenCES may need to be adapted or reconsidered for use within intellectual disability services following their study with forensic intellectual disability SUs. Thus, we suggest that the EssenCES be adapted-using input from speech and language therapy-to facilitate access for LD adolescent SUs through developing SU-rated EssenCES for neurodevelopmental CAMHS settings, with an emphasis on visual aids.…”
Section: Recommendationsmentioning
confidence: 99%
“…In contrast, Quinn et al (2012) found initial evidence to support the proposal that the EssenCES was a reliable tool for use with LD secure service population. More recently, however, Chester et al (2015) gathered qualitative data from clinicians who were experienced in administering the EssenCES with a forensic intellectual disability population and garnered results which reflected clinician concerns over patient comprehension of items, around clinician support and interpretation, and of data reliability. In contrast, Willets et al (2014) conducted an EssenCES study which compared LD and non-LD psychiatric services and found that SUs in both services did not differ in their perceptions of social climate.…”
Section: Introductionmentioning
confidence: 99%